PENGARUH KANDUNGAN INFORMASI LABA, ARUS KAS OPERASI, DEVIDEN, UKURAN PERUSAHAAN DAN TINGKAT INFLASI TERHADAP ABNORMAL RETURN - Nana Umdiana (Universitas Serang Raya, 2014)
Object of this research find the effect of profit information, cash flow of operation, deviden, size firm and inflation to Abnormal Return. The Sample of this research is the industrial sector consumption Manufacturing company listed on the Jakarta Stock Exchange in 2008-2012 by using the method purposive sampling. There were 6 companies for sampel this research. Analysis method used is multiple regression, this for analysis effect of independen variable to dependen variable, to parsial or simultan. The test results showed that information affect the earnings and dividend increase to abnormal return. This study failed to explain the effect of operating cash flow, company size and inflation of the abnormal return. this indicates that investors will prefer informassi earnings and dividends in making decisions in comparison with operating cash flow, company size and inflation. Keys Word : Profit Information, Operating Cash Flow, Deviden, Size Firm, Inflation, Abnormal Return